Analysis of Student Learning Outcomes According to the Implementation of the Project Based Learning - Wahid S*, Syamsul (Physics Education, 2025)
This research aims to determine the learning outcomes according to the project-based learning at the Statistics course of the Physics Department, Faculty of Mathematics and Natural Sciences, Makassar State University. The type of research is descriptive survey research to obtain quantitative data. The population in this study were all students in the Physics Department, class of 2023/2024 who are currently in semester 3 consisting of 4 classes with a total of 93 students. The total sample in this study was 65 people. The sampling technique in this study used purposive sampling. The variables in this study were learning outcomes and project-based learning. The data obtained showed that the learning outcomes of the statistics course of the Physics Department, Faculty of Mathematics and Natural Sciences, Makassar State University were mostly in the very high category with a percentage reaching 90%. The learning outcome value factor was very high because students understood the material given by the lecturer very well, strong learning motivation and effective learning strategies were applied. The learning model used by lecturers in the statistics course in the Physics Department is the Project Based Learning model.